v.4 - "Gour, Hari Singh" (Allahabad, 1998)
This book is a useful practical and definitive guide to Criminal Law practitioners at the Bar, at every level of experience, Courts, Police & Prosecution Forces seeking to understand the provisions of this substantive law.
Keywords: Penal code